2015
DOI: 10.2174/1574887110666150127110314
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Counseling for Hereditary Breast and Ovarian Cancer Among Puerto Rican Women Living in the United States

Abstract: Background-Little is known about barriers to Hereditary Breast and Ovarian Cancer (HBOC) genetic counseling among Puerto Rican women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Similarly, few reviews included "use of theory" as a coding category. Finally, only 1 of the 24 reviews focused exclusively on an ethnic minority population [35], and several others noted the lack of diversity in published studies included in their reviews and the need for more research with ethnic minority groups [36][37][38]. Table 2 provides additional information about the methods and use of theory in the included reviews.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, few reviews included "use of theory" as a coding category. Finally, only 1 of the 24 reviews focused exclusively on an ethnic minority population [35], and several others noted the lack of diversity in published studies included in their reviews and the need for more research with ethnic minority groups [36][37][38]. Table 2 provides additional information about the methods and use of theory in the included reviews.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Eight papers reviewed information about baseline knowledge, attitudes, and perceptions that individuals have about CGT [35,36,[39][40][41][42][43][44]. The reviews suggest that, to date, studies of CGT knowledge and attitudes have primarily focused on two groupsthe public and health care providers.…”
Section: Baseline Knowledge and Attitudes About Genetic Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study examining the preferences for health education information concerning HBOC among at-risk Latina women found that preferences varied by subethnicity, specifically Mexican, Puerto Rican and Cuban (Quinn et al 2011). To date, only one study has evaluated barriers and facilitators to the use of BRCA genetic counseling exclusively among Latinas at-risk for HBOC of Puerto Rican descent (Scherr et al 2014). It will be useful to translate these research efforts to discover the unique factors that may impact use of genetic services among a broader group of Latinas based on country of origin.…”
Section: Research Recommendationsmentioning
confidence: 99%